Differences in Knowledge and Attitudes Towards Hypertension Prevention Through Poster Media with the Think Pair Share Method - Happy Aprilia Belkis; Nova Muhani; Dhiny Easter Yanti; Lolita Sary (Persatuan Dosen Kesehatan Masyarakat, 2025)
Hypertension is now a health problem that is not only experienced by the elderly, but also by adolescents who are at risk of experiencing high blood pressure due to bad habits and unhealthy lifestyles. The prevalnce of hypertension in Lampung Province is 15,10 % of the 6,216,638 population aged 15 years and over. The high cases of hypertension in adolescensts today are caused by one of the low knowledge and attitudes about the risk factors for hypertension. It is necessary to in increase adolescent knowledge and attitudes thourgh poster media with the think pair share method, which is not yet known how effective this method is in increasing knowledge and attitudes in adolescent student.The purpose of this study was to determine the differences in knowledge and attitudes towards preventing hypertension in adolescents through poster media with the think pair share method at SMA IT Baitul Jannah Bandar Lampung in 2025. This study used a quantitative research design with a quasi experimental approach. The population of the study was from grades 10 and 11, namely 185 students. The sampling technique wa proposional simple random sampling. Data collection techniques through questionnaire sheets. Data analysis used unvariate (frequency distribution) and bivariate (wilcoxon). The results showed that there were differences in knowledge (p-value = 0,001) and attitude (p-value = 0,001) ) and attitude (p-value = 0,001) with poster media and the think pair share method. It is expected that schools will use posters with the think pair share method when providing hypertension counseling materials.